Short and long-run behaviour of long-term sovereign bond yields - António Afonso (Center for Economic Studies and ifo Institute (CESifo), 2010)
This study assesses the short and long-run behaviour of long-term sovereign bond yields in OECD countries, for the period 1973-2008. We employ a dynamic panel approach to reflect financial and economic integration, and to increase the performance and accuracy of the tests. Given the existence of cross-country dependence regarding sovereign yields and its determinants, we resort to simulation and bootstrap methods for the analysis. Results based on the Common Correlated Effect estimator of Pesaran (2006) and on Panel Error Correction Models to sort out short- and long-run fiscal developments show that in addition to common movements in sovereign yields, investors also consider country differences arising from specific factors (inflation, budgetary and current account imbalances, real effective exchange rates, and liquidity).
Keywords: C23; E43; E62; G15; H62; 330; long-term yields; EU; financial integration; panel cointegration; bootstrap; Rendite; Öffentliche Anleihe; Laufzeit; Internationaler Finanzmarkt; Marktintegration; Schätzung; OECD-Staaten; EU-Staaten